Se-m diatomic catalyst, and preparation method and application thereof

CN117913294BActive Publication Date: 2026-10-27ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410090150.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2026-10-27
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

[0009]本发明的目的就在于克服现有的技术问题,为解决现有双原子催化剂技术方案中双原子位点比例低、稳定性不佳的问题,本发明提供了一种Se-M双原子催化剂的简便制备方法,Se-M双原子与N6-空穴中的四个氮原子配位结合而均匀稳定地分步在类石墨烯二维C2N载体上

Benefits of technology

[0052]本发明工艺简单,操作方便本发明采用熔融盐法和酸刻蚀法制备了二维C2N薄片,它具有周期均匀分布的N6-空穴来锚定毗邻的双原子。利用分步热解锚定策略来调整固定在C2N薄片上的双原子催化剂。Se-M双原子催化剂应用于氧还原中,表现出优异的催化活性和稳定的循环寿命。因此,制备Se-M双原子催化剂并用于改善氧还原性能是构建高性能锌空电池和燃料电池很有前途的途径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117913294B_ABST
    Figure CN117913294B_ABST
Patent Text Reader

Abstract

The application relates to the fields of diatomic catalyst preparation and battery energy storage, and relates to a preparation method of a Se-M diatomic catalyst, which comprises the following steps: synthesis of C2N, synthesis of Se-C2N, and synthesis of the Se-M diatomic catalyst. The application has the advantages of simple process and convenient operation; two-dimensional C2N sheets are prepared by adopting a molten salt method and an acid etching method, the two-dimensional C2N sheets have uniformly-distributed N6-holes to anchor adjacent diatomic atoms; a step-by-step pyrolysis anchoring strategy is used to adjust the diatomic catalyst fixed on the C2N sheets; the Se-M diatomic catalyst is applied to oxygen reduction, and excellent catalytic activity and stable cycle life are exhibited. Therefore, the preparation of the Se-M diatomic catalyst and the application of the Se-M diatomic catalyst to the improvement of oxygen reduction performance are a promising way to construct high-performance zinc-air batteries and fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of diatomic catalyst preparation and battery energy storage, and in particular to a Se-M diatomic catalyst, its preparation method, and its application. Background Technology

[0002] The rapid development of novel energy storage and conversion devices has spurred a high demand for advanced electrocatalysts. The electrocatalytic oxygen reduction reaction (ORR), as the cathode process in metal-air batteries and fuel cells, suffers from slow kinetics that severely limit its energy conversion efficiency. Platinum (Pt)-based catalysts are primarily used for catalyzing ORR at the cathode. However, the high cost and natural scarcity of platinum-based catalysts hinder their practical application. To replace platinum group metals (PGMs), there is an urgent need to develop non-precious metal electrocatalysts with high catalytic activity and long durability. This has fueled strong interest in developing high-performance ORR electrocatalysts.

[0003] Single-atom catalysts have attracted researchers' attention due to their near 100% atom utilization and excellent catalytic performance. Among them, carbon-supported single-atom catalysts with atomic metal-nitrogen sites (especially Fe-NC) are highly active candidates for the electrocatalytic ORR reaction. The catalytic activity of the N-coordinated Fe sites with high electronegativity is closely related to their symmetrical electron distribution, which leads to their catalytic activity towards oxygen intermediates (e.g., * O2, * O、 * OOH and * The adsorption energy of OH is not ideal. Furthermore, oxygen intermediates prefer to adsorb onto the active site via lateral or end-position models, which inevitably leads to a high energy barrier for OO bond breaking, making further performance enhancement challenging.

[0004] Diatomic catalysts (DACs) exhibit superior catalytic performance in energy storage and conversion, chemical synthesis, and environmental protection. Compared to single-atom catalysts (SACs), DACs typically have higher metal loadings and more complex and flexible active sites.

[0005] Constructing diatomic catalysts (DACs) can improve ORR performance. These catalysts typically exhibit strong interactions between two adjacent sites: 1) Diaatomic sites may alter the adsorption energy of intermediates by enhancing oxygen adsorption capacity. 2) Diaatomic sites may lower the reaction energy barrier through electronic and concerted effects. 3) Due to the concerted effect on oxygen-containing intermediates at both sites, diatomic sites may alter the reaction pathway and accelerate reaction kinetics. Therefore, the adsorption state of ORR intermediates can be well tunable at diatomic sites, which is beneficial for OO bond cleavage and thus holds promise for enhancing oxygen reduction catalytic activity.

[0006] However, the development of DACs is still in its early stages and several challenges remain. 1) Inhomogeneous defects and cavities in the support during synthesis make it difficult to precisely control the accurate configuration and uniform dispersion of diatomic sites. Therefore, single-atom sites or clusters inevitably appear on the support coupled with diatomic sites. Furthermore, although DACs can increase the loading of active sites compared to SACs, excessive metal loading can still lead to the aggregation of active sites. In addition, DACs still face the risk of active site loss, aggregation, or reconstruction during catalysis. 2) General characterization techniques, such as aberration-corrected dark-field scanning transmission electron microscopy (AC HAADF-STEM), Spectroscopy and other methods cannot, to a certain extent, identify the accurate coordination environment of diatomic active sites, thus hindering the true correlation between catalytic activity and specific active sites.

[0007] Currently, the synthesis of DACs can be broadly categorized into two main strategies: top-down and bottom-up. Top-down methods rely on input energy to disperse previously aggregated metals into diatomic particles, such as ball milling and atom trapping. Bottom-up strategies select precursors with binuclear metal centers or supports with binuclear anchoring sites, synthesizing DACs through methods such as pyrolysis, impregnation, atomic layer deposition, and ion exchange. Ball milling and atom trapping can provide high-quality DACs, but they are only applicable in limited situations. Binuclear metal-center precursors have a strong tendency to polymerize under harsh synthesis conditions, so this strategy is often carried out under mild conditions such as low temperature or photodecomposition. However, mild synthesis conditions weaken the interaction between the metal sites and the support, reducing catalyst stability. Pyrolysis of multiple metal precursors premixed with the host material is the most common method for introducing multi-metal centers onto a single support. This method endows the material with a wide range of elemental combinations, but the coexistence of large numbers of single-atom and diatomic sites remains a challenge.

[0008] Therefore, there is an urgent need for a Se-M diatomic catalyst, its preparation method, and its application to solve the above-mentioned technical problems. Summary of the Invention

[0009] The purpose of this invention is to overcome the existing technical problems. In order to solve the problems of low proportion of diatomic sites and poor stability in existing diatomic catalyst technology, this invention provides a simple preparation method of Se-M diatomic catalyst. Se-M diatomic atoms coordinate with the four nitrogen atoms in N6-hole and are uniformly and stably distributed on graphene-like two-dimensional C2N support.

[0010] To achieve the above objectives, the present invention is implemented according to the following technical solution:

[0011] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0012] Synthesis of S1 and C2N:

[0013] S1.1 Cyclohexanehexanone octahydrate and urea were ground and mixed to obtain a mixture; the mixture was heated to obtain an organic crosslinked compound;

[0014] S1.2 The organic crosslinking material was ground and mixed with MgCl2 to obtain a mixed sample; the mixed sample was annealed under an inert atmosphere to obtain an annealed product;

[0015] S1.3 The annealed product was placed in an acidic solution, stirred and etched, then washed and dried to obtain C2N;

[0016] Synthesis of S2, Se-C2N:

[0017] The C2N obtained in step S1.3 was ground and mixed with selenium dioxide and pyromellitic acid, and then annealed in an inert atmosphere to obtain Se-C2N;

[0018] Synthesis of S3, Se-M diatomic catalysts:

[0019] S3.1 Take Se-C2N and place it in anhydrous ethanol. Stir and then add acetylacetone metal salt. Mix well and then evaporate the ethanol to obtain a precursor mixture.

[0020] S3.2 The precursor mixture was annealed under an inert atmosphere to obtain the Se-M diatomic catalyst SeM-C2N.

[0021] The Se-M diatomic catalyst SeM-C2N specifically consists of Se-M diatomic atoms supported on C2N, where M refers to one of the metal elements Fe, Mn, Co, Ni, Cu, and Mo.

[0022] Preferably, in step S1.1, the molar ratio of cyclohexanehexanone octahydrate to urea is 1:4.5; the heating temperature is 70-100℃; and the heating time is 20-50 min.

[0023] Preferably, in step S1.2, the mass ratio of the organic crosslinker to MgCl2 is 1:2.5-6; the annealing temperature is 800-1100℃; and the annealing time is 1-3h.

[0024] Preferably, in step S1.3, the acidic solution is a 0.5 mol / L H2SO4 solution; the stirring time is 4-16 h.

[0025] Preferably, in step S2, the mass ratio of C2N, selenium dioxide, and trimesic acid is 1:(0.5-1.5):(0-0.3).

[0026] The annealing process is as follows: The annealing process includes two stages. The first stage annealing temperature is 200-400℃ and the first stage annealing time is 10-90 min. The second stage annealing temperature is 800-1100℃ and the second stage annealing time is 1-3 h.

[0027] Preferably, in step S3.1, the mass ratio of Se-C2N to acetylacetone metal salt is 10-30:1; the stirring time is 4-20 h; and the evaporation temperature is 60-100 °C.

[0028] Preferably, in step S3.1, the acetylacetone metal salt is one of iron acetylacetone, manganese acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, and molybdenum acetylacetone.

[0029] Preferably, in step S3.2, the annealing temperature is 800-1100℃ and the annealing time is 1-3h.

[0030] Specifically, it includes the following steps:

[0031] Synthesis of S1 and C2N:

[0032] S1.1 Take cyclohexanehexanone octahydrate and urea (molar ratio of 1 mmol: 4.5 mmol) and grind them thoroughly in an agate mortar. Transfer the ground mixture to a 25 mL pressure-resistant bottle and gently heat it in an oil bath to form a deep orange viscous organic crosslinking compound.

[0033] In step S1.1, the grinding time is 10-60 min; the heating temperature is 70-100℃; and the heating time is 20-50 min.

[0034] S1.2 The formed organic crosslinked material and anhydrous MgCl2 white powder are ground thoroughly in an agate mortar at a certain mass ratio. The resulting uniformly mixed sample is annealed under an inert atmosphere and then cooled naturally to obtain the annealed product.

[0035] In step S1.2, the mass ratio of the organic crosslinked material to anhydrous MgCl2 is 1:2.5-6; the grinding time is 20-120 min; the inert atmosphere is at least one of nitrogen, argon, and helium; and the heating rate during the annealing process is 1-5℃ / min. -1 The annealing temperature is 800-1100℃; the annealing time is 1-3 hours.

[0036] S1.3 The annealed product was thoroughly ground in an agate mortar and then placed in a certain volume of 0.5M (0.5mol / L) H2SO4 solution, and etched by stirring at room temperature for a certain period of time. Subsequently, it was washed repeatedly with a large amount of deionized water until the solution was neutral (pH=7). Finally, it was dried in a vacuum oven at 60℃ to obtain the two-dimensional carbon material C2N.

[0037] In step S1.3, the grinding time is 10-60 min; the volume of H2SO4 solution is 100-250 mL; and the stirring time is 4-16 h.

[0038] Synthesis of S2, Se-C2N:

[0039] C2N, selenium dioxide (SeO2), and pyromellitic acid (C9H6O6) were mixed in a certain mass ratio and thoroughly ground. The mixture was then subjected to two stages of annealing at a certain temperature under an inert atmosphere and allowed to cool naturally to obtain Se-C2N.

[0040] In step S2, the mass ratio of C2N, selenium dioxide, and trimesic acid is 1:(0.5-1.5):(0-0.3); the grinding time is 10-60 min; the inert atmosphere is at least one of nitrogen, argon, and helium; the two-stage annealing treatment is as follows: the first stage heating rate is 1-5℃ / min. -1 The first stage annealing temperature is 200-400℃, and the first stage annealing time is 10-90 min; the second stage heating rate is 1-5℃ / min. -1 The second-stage annealing temperature is 800-1100℃, and the second-stage annealing time is 1-3 hours.

[0041] Synthesis of S3, Se-M diatomic catalysts:

[0042] S3.1 Take a certain amount of Se-C2N powder and place it in anhydrous ethanol. After stirring for 30 min, add acetylacetone metal salt and stir continuously for 4-20 h to make it fully and evenly mixed. Then, evaporate the solvent ethanol in an oven to obtain the precursor mixture.

[0043] In step S3.1, the mass ratio of Se-C2N to acetylacetonate metal salt is 10-30:1; the evaporation temperature is 60-100℃; and the acetylacetonate metal salt is iron(III)acetylacetonate (C 15 H 21 FeO6), manganese acetylacetonate (C 10 H 14MnO4), Cobalt(II)acetylacetonate, C 10 H 14 O4Co), Nickel(II)acetylacetonate, NiC 10 H 14 O4), Copper(II)acetylacetonate, C 10 H 14 CuO4), molybdenum acetylacetonato (Bis(acetylacetonato)dioxomolybdenum(VI), C 10 H 14 One of the MoO6).

[0044] S3.2 The precursor mixture was annealed at a certain temperature under an inert atmosphere and then allowed to cool naturally to obtain the Se-M diatomic catalyst.

[0045] In step S3.2, the inert atmosphere is at least one of nitrogen, argon, and helium; the annealing heating rate is 1-5℃ / min. -1 The annealing temperature is 800-1100℃, and the annealing time is 1-3h.

[0046] This invention discloses the application of Se-M diatomic catalysts in electrocatalytic oxygen reduction reactions.

[0047] Mechanism of action:

[0048] C2N, a unique member of the carbon nitride family, is a porous two-dimensional crystal with periodically distributed holes. Furthermore, C2N exhibits a graphene-like structure, where one-third of the carbon atoms are replaced by pyrazine nitrogen atoms. This results in a covalent zeolite-type structure in C2N, where the pores are uniformly distributed (ideally with 12 atom-sized N6-holes). C2N's unique porous structure generates a large π-electron pool within the benzene ring and an intrinsic electron density on the nitrogen atoms. Introducing nitrogen atoms into the carbon lattice enhances the properties of carbon materials, such as chemical and thermal stability, band structure, catalytic efficiency, and oxidation stability, and facilitates specific interactions with liquids, solvated ions, or gases. Its uniformly distributed pore structure is rich in free unsaturated nitrogen sites, acting like "clamps" to trap metal sites. Therefore, metal precursors can be precisely trapped by the periodically distributed N6-holes, anchoring the metal sites firmly to the N ligands. Thus, C2N monolayers are excellent supports for diatomic catalysts, allowing for precise control of the accurate configuration and uniform dispersion of diatomic sites. Furthermore, X-ray absorption fine structure spectroscopy (XAFS) can further identify the precise coordination environment of diatomic active sites and explore the structure-activity relationship between catalytic activity and specific active sites.

[0049] Two-dimensional C2N graphene-like nanoparticles possess periodically distributed N6- vacancies, rich in free unsaturated nitrogen sites, acting like "clamps" to trap metal sites. Therefore, metal precursors can be precisely captured by these vacancies, firmly locking the metal sites onto the N ligands. While Chinese invention patent CN106475081A, "A C2N Graphene Composite Noble Metal Nanocatalyst and Its Preparation Method," also uses C2N, its C2N graphene support preparation method is complex and time-consuming, and the introduction of noble metal nanoparticles significantly increases the catalyst manufacturing cost.

[0050] This invention synthesizes SeM-C2N via a molten salt method, acid etching, and stepwise high-temperature pyrolysis. First, cyclohexanehexanone octahydrate and urea are ground in a specific molar ratio, breaking down large particles into smaller ones to form a uniformly distributed mixture. The mixture is then gently heated at 70-100°C (below the melting points of the respective components), causing liquefaction and indicating a deep eutectic process. Simultaneously, the powder mixture changes from off-white to deep orange. During this organic crosslinking process, water and gases escape from the precursor components. The resulting organic crosslinked material is then ground and mixed with anhydrous MgCl2 and pyrolyzed at 800-1100°C. The molten MgCl2 (melting point 714°C) acts as a hard template agent during the carbonization of the carbon source, yielding the graphene-like two-dimensional carbon material C2N. Subsequently, the mixture of C2N, SeO2, and trimesic acid is calcined at 800-1100℃. At this high temperature, SeO2 is reduced by carbon (C) to individual Se atoms, which are then anchored on C2N, resulting in a single-atom Se-C2N. At 800-1100℃, nitrogen atoms on C2N vaporize and escape, with trimesic acid acting as a supplementary nitrogen source and maintaining the periodic hole structure of C2N. Subsequently, the precursor acetylacetone salt spontaneously adsorbs and impregnates into the high specific surface area of ​​Se-C2N, and is thermally reduced to individual metal atoms at 800-1100℃. Because the single Se atom is uniformly anchored on C2N first (one Se atom is firmly coordinated with two N atoms), the metal atom subsequently reduced by carbon (C) attracts and bonds with the previously anchored Se in the N6- vacancy, and then bonds with the two N atoms at the opposite position, forming a strong SeM-N4 diatomic structure. Finally, after naturally cooling to room temperature, the solid was collected to obtain the Se-M diatomic catalyst SeM-C2N.

[0051] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0052] This invention features a simple and convenient process. A two-dimensional C2N sheet is prepared using a molten salt method and acid etching, which anchors adjacent diatomic atoms through a periodically uniformly distributed N6- vacancy. A stepwise pyrolysis anchoring strategy is employed to modulate the diatomic catalyst immobilized on the C2N sheet. The Se-M diatomic catalyst exhibits excellent catalytic activity and stable cycle life in oxygen reduction. Therefore, preparing Se-M diatomic catalysts and using them to improve oxygen reduction performance is a promising approach for constructing high-performance zinc-air batteries and fuel cells. Attached Figure Description

[0053] Figure 1 This is a flowchart of the SeFe-C2N diatomic catalyst prepared in Example 1 of the present invention;

[0054] Figure 2 The image shows a transmission electron microscope (TEM) image of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention.

[0055] Figure 3 The X-ray diffraction (XRD) pattern of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention;

[0056] Figure 4 The Raman spectrum of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention is shown below.

[0057] Figure 5 The nitrogen isothermal adsorption-desorption curve of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention;

[0058] Figure 6 Aberration-corrected electron microscopy image of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention;

[0059] Figure 7 Synchrotron radiation diagram of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention;

[0060] Figure 8 The diagram shows the oxygen reduction performance of the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention.

[0061] Figure 9 The oxygen reduction cycle stability diagram is shown for the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention.

[0062] Figure 10 The electron transfer number diagram is shown for the SeFe-C2N diatomic catalyst prepared in Example 1 of this invention.

[0063] Figure 11The X-ray diffraction (XRD) patterns of the Se-M diatomic catalyst SeM-C2N prepared in Examples 2-6 of this invention are shown below.

[0064] Figure 12 The images show the Raman spectra of the Se-M diatomic catalyst SeM-C2N prepared in Examples 2-6 of this invention.

[0065] Figure 13 The graph shows the oxygen reduction performance of the Se-M diatomic catalyst SeM-C2N prepared in Examples 2-6 of this invention.

[0066] Figure 14 These are aberration-corrected electron micrographs of the Se-M diatomic catalyst SeM-C2N prepared in Examples 2-6 of this invention.

[0067] Figure 15 Synchrotron radiation diagrams of the Se-M diatomic catalyst SeM-C2N prepared in Examples 2-6 of this invention;

[0068] Figure 16 The images show transmission electron microscopy (TEM) and aberration electron microscopy (SEM) images of the Fe-C2N single-atom catalyst prepared in Comparative Example 2 of this invention. Detailed Implementation

[0069] The present invention will be further described below with reference to specific embodiments. The illustrative embodiments and descriptions herein are used to explain the present invention, but are not intended to limit the present invention.

[0070] All raw materials used in this invention are not particularly restricted in their source and can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0071] The devices involved in this invention are not particularly limited to those commonly used in the field, and their operation and usage are well known to those skilled in the art.

[0072] In this invention, the specific electrochemical measurements of ORR are as follows:

[0073] All electrochemical tests were performed at room temperature using an electrochemical station (CHI 760E, CH Instrument Co., Ltd, Shanghai, China) equipped with a rate controller (Pine Co., Ltd., USA). The three-electrode system for ORR measurements using 0.1M KOH electrolyte consisted of a catalyst-coated glassy carbon rotating disk electrode (GC-RDE, disk diameter 5 mm, surface area 0.196 cm²). -2 The electrode used is the working electrode, the saturated calomel electrode (SCE) is the reference electrode, and platinum is the counter electrode. All potentials used in this work are calibrated to the reversible hydrogen electrode (RHE) according to the Nernst equation.

[0074] E RHE =E (SCE) +0.2415 +0.592 × pH

[0075] Electrocatalyst ink was obtained by ultrasonically dispersing 2 mg of catalyst in a mixed solution consisting of 180 μL ethanol, 60 μL H2O, and 10 μL Nafion (5 wt%). Subsequently, 10 μL of homogeneous ink was dropped onto a catalyst loading of 0.4 mg / cm³. 2 The catalyst was allowed to air dry on an RDE glassy carbon electrode. Cyclic voltammetry (CV) tests were performed on the catalyst under N2 / O2 saturated electrolyte at a scan rate of 50 mV·s. -1 Linear sweep voltammetry (LSV) measurement is performed in an O2-saturated solution at a rate of 5 mV·s. -1 The measurement was taken at a rotational speed of 1600 rpm with a scanning rate.

[0076] The present invention will be further described below with reference to specific embodiments. The illustrative embodiments and descriptions herein are used to explain the present invention, but are not intended to limit the present invention.

[0077] Example 1

[0078] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0079] 1) Synthesis of C2N

[0080] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, the mixture was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0081] 2) Synthesis of Se-C2N

[0082] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:1:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1000℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0083] 3) Synthesis of SeFe-C2N

[0084] The obtained 90 mg Se-C2N and 6 mg acetylacetone iron(III) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated in an oven at 80 °C. Then, the carbon material uniformly impregnated with iron salts was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 900℃ and held for 2 hours. After natural cooling to room temperature, the calcined carbon sample was collected to obtain SeFe-C2N, which can be used directly without further processing.

[0085] like Figures 1 to 10 As shown, Figure 1 The synthesis process of SeFe-C2N is shown.

[0086] Figure 3 , Figure 4 , Figure 5 , Figure 8 In this document, the C2N described is prepared in step 1) of Example 1; the Se-C2N described is prepared in step 2) of Example 1; the SeFe-C2N described is prepared in step 3) of Example 1; and the Fe-C2N described is prepared in step 2) of Comparative Example 2.

[0087] Transmission electron microscopy (TEM) Figure 2 This indicates that SeFe-C2N possesses a two-dimensional nanosheet structure. Neither metal nor metal oxides were observed, which is consistent with powder X-ray diffraction (PXRD) patterns. Figure 3 The results are consistent, indicating the atomic dispersion state of Se and Fe atoms. Raman spectroscopy ( Figure 4 The defects in SeFe-C2N were analyzed. Two distinct main peaks were observed in the D band (disordered carbon) and the G band (graphite carbon), located at 1372.6 and 1594.5 cm⁻¹, respectively. -1 Calculate the I of SeFe-C2N. D / I GA value of 0.94 (lower than Se-C2N and C2N) indicates a high degree of graphitization, which is beneficial for electron transfer and the stability of active sites during ORR. Nitrogen adsorption-desorption isotherms ( Figure 5 This indicates that SeFe-C2N has a large surface area (1165.1 m²). 2 g -1 The large specific surface area and abundant mesopores (1.4 nm) of SeFe-C2N are beneficial for the exposure of catalytic sites. SeFe-C2N is a C2N (1868.6 nm) formed during the high-temperature evaporation of MgCl2. 2 g -1 Inherited from (1nm). Aberration-corrected high-angle annular dark-field scanning image (HAADF-STEM) further reveals structural and state information of the metal. For example... Figure 6 As shown, the absence of Se or Fe nanoparticles further indicates atomic dispersion of Se and Fe. Notably, both diatomic sites (highlighted with yellow ellipses) and monoatomic sites (highlighted with blue circles) are observed, suggesting the possibility of anomalous active sites. The bimetallic atomic sites account for approximately 82% of the dominant metallic sites in SeFe-C2N. The distance between adjacent Se and Fe atoms is observed to be approximately... This closely matches the effective diameter of Se / Fe atoms in the metal, indicating the stable existence of the diatomic Se-Fe site. Synchrotron radiation testing ( Figure 7 This further confirms the successful preparation of the SeFe diatomic catalyst. The C2N-supported SeFe diatomic catalyst (SeFe-C2N) can achieve a high half-wave potential of 0.926 V vs. RHE in 0.1 M KOH electrolyte. Figure 8 After 10,000 cycles, the half-wave potential only decays by 16mV. Figure 9 KL equation and rotating disk-to-disc electrode test ( Figure 10 This indicates that the ORR process is a typical 4-electron transfer process.

[0088] Example 2

[0089] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0090] 1) Synthesis of C2N

[0091] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 80 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:2.5. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, the mixture was heated at 3 °C for 3 min. -1 The carbon sample was heated to 800℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 100 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0092] 2) Synthesis of Se-C2N

[0093] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:0.5:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 900℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was removed to obtain Se-C2N.

[0094] 3) Synthesis of SeMn-C2N

[0095] The obtained 90 mg Se-C2N and 4 mg manganese acetylacetone(II) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated to dryness in an oven at 80 °C. Then, the carbon material uniformly impregnated with manganese salt was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The carbon sample was heated to 800℃ at a certain heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was collected to obtain SeMn-C2N, which can be used directly without further processing.

[0096] Example 3

[0097] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0098] 1) Synthesis of C2N

[0099] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 100 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:6. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, the mixture was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 3 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0100] 2) Synthesis of Se-C2N

[0101] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:1.5:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1100℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0102] 3) Synthesis of SeMo-C2N

[0103] The obtained 90 mg Se-C2N and 3 mg molybdenum acetylacetonate (VI) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated to dryness in an oven at 80 °C. Then, the carbon material uniformly impregnated with molybdenum salt was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 1000℃ and held for 2 hours. After natural cooling to room temperature, the calcined carbon sample was collected to obtain SeMo-C2N, which can be used directly without further processing.

[0104] Example 4

[0105] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0106] 1) Synthesis of C2N

[0107] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, it was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0108] 2) Synthesis of Se-C2N

[0109] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:1:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1000℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0110] 3) Synthesis of SeCu-C2N

[0111] The obtained 90 mg Se-C2N and 3 mg copper acetylacetonate (II) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated in an oven at 80 °C. Then, the carbon material uniformly impregnated with copper salt was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 900℃ and held for 3 hours. After natural cooling to room temperature, the calcined carbon sample was collected to obtain SeCu-C2N, which can be used directly without further processing.

[0112] Example 5

[0113] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0114] 1) Synthesis of C2N

[0115] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, it was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0116] 2) Synthesis of Se-C2N

[0117] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:1:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1000℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0118] 3) Synthesis of SeCo-C2N

[0119] The obtained 90 mg Se-C2N and 4 mg cobalt(II) acetylacetonate were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated in an oven at 80 °C. Then, the carbon material uniformly impregnated with cobalt salt was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 900℃ and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was collected to obtain SeCo-C2N, which can be used directly without further processing.

[0120] Example 6

[0121] A method for preparing a Se-M diatomic catalyst includes the following steps:

[0122] 1) Synthesis of C2N

[0123] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, it was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid (H₂SO₄) and acid-washed for 12 hours to etch away residual MgCl₂ and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C₂N.

[0124] 2) Synthesis of Se-C2N

[0125] C2N, selenium dioxide (SeO2), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:1:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1000℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0126] 3) Synthesis of SeNi-C2N

[0127] The obtained 90 mg Se-C2N and 4 mg nickel acetylacetonate (II) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated in an oven at 80 °C. Then, the carbon material uniformly impregnated with nickel salt was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 900℃ and held for 2 hours. After natural cooling to room temperature, the calcined carbon sample was collected to obtain SeNi-C2N, which can be used directly without further processing.

[0128] like Figures 11 to 15 The figures shown are characterization diagrams of SeMn-C2N, SeMo-C2N, SeCu-C2N, SeCo-C2N, and SeNi-C2N prepared in Examples 2-6. Figure 11 The corresponding X-ray diffraction (XRD) pattern; Figure 12The corresponding Raman spectrum is shown below. Figure 13 The corresponding oxygen reduction performance diagram; Figure 14 The corresponding spherical aberration electron microscope image; Figure 15 This is the corresponding synchrotron radiation map.

[0129] Comparative Example 1

[0130] The difference between Comparative Example 1 and Example 1 is that the process of introducing Fe element is omitted, and the type and amount of Se source are different; otherwise, they are the same as in Example 1, yielding Se-C2N. The specific process is as follows:

[0131] 1) Synthesis of C2N

[0132] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, the mixture was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0133] 2) Synthesis of Se-C2N

[0134] C2N, selenium powder (Se), and trimesic acid (C9H6O6) were thoroughly ground and mixed in a mass ratio of 1:0.7:0.2, then transferred to a corundum ceramic boat and placed in the middle of a tube furnace. The mixture was then incubated at 3°C ​​for [time missing] minutes under nitrogen protection. -1 After heating to 300℃ at a certain heating rate and holding for 0.5 hours, continue heating at a rate of 3℃ / min. -1 The temperature was increased to 1000℃ and held for 1 hour. After natural cooling to room temperature, the calcined carbon sample was taken out to obtain Se-C2N.

[0135] Comparative Example 2

[0136] The difference between Comparative Example 2 and Example 1 is that the process of introducing Se element is omitted; otherwise, it is the same as Example 1, yielding Fe-C2N. The specific process is as follows:

[0137] 1) Synthesis of C2N

[0138] First, cyclohexanehexanone octahydrate (12 mmol) and urea (54 mmol) were thoroughly ground in an agate mortar for 30 min. The ground mixture was transferred to a 25 mL pressure-resistant bottle and gently heated in an oil bath at 90 °C for 0.5 h to form a deep orange viscous organic crosslinker. Then, the formed organic crosslinker was thoroughly ground in an agate mortar with anhydrous MgCl2 white powder at a mass ratio of 1:3.75. Subsequently, the resulting mixture was transferred to a corundum ceramic boat and placed in the middle of a tube furnace. Under nitrogen protection, the mixture was heated at 3 °C for 3 min. -1 The carbon sample was heated to 900℃ at a controlled heating rate and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was removed and ground into powder. The powder was then transferred to 250 mL of 0.5 mol / L sulfuric acid solution and acid-washed for 12 hours to etch away residual MgCl2 and MgO. After acid washing, the sample was repeatedly washed with a large amount of deionized water until the solution was neutral (pH = 7). Finally, it was dried in a vacuum oven at 60℃ for 12 hours to obtain the two-dimensional carbon material C2N.

[0139] 2) Synthesis of Fe-C2N

[0140] The obtained 90 mg C2N and 6 mg acetylacetone iron(III) were added to 100 mL of ethanol and stirred for 12 h. After stirring, the solvent ethanol was evaporated in an oven at 80 °C. Then, the carbon material uniformly impregnated with iron salts was placed in a corundum ceramic boat and incubated at 3 °C for 1 minute under nitrogen protection. -1 The temperature was increased to 900℃ and held for 2 hours. After naturally cooling to room temperature, the calcined carbon sample was collected to obtain Fe-C2N, which can be used directly without further processing.

[0141] like Figure 16 As shown, Figure 16 Transmission electron microscopy (TEM) and aberration electron microscopy (SEM) images of the Fe-C2N single-atom catalyst prepared for Comparative Example 2.

[0142] Compared to the selenium powder in Comparative Example 1, the Se source (SeO2) in this example is less toxic and safer to use. Furthermore, there is a significant performance difference between the example (Se-M diatomic catalyst) and the comparative example (single-atom catalyst). In SeFe-C2N, the successive coordination of Se and Fe with N forms a robust asymmetric SeM-N4 configuration, which greatly enhances the oxygen reduction activity and stability of SeFe-C2N.

[0143] This invention utilizes a molten salt method and acid etching to prepare two-dimensional C2N sheets with periodically uniformly distributed N6- holes anchoring adjacent diatoms. A stepwise pyrolysis anchoring strategy is employed to modulate the diatomic catalyst immobilized on the C2N sheet. The Se-M diatomic catalyst exhibits excellent catalytic activity and stable cycle life in oxygen reduction. Therefore, preparing Se-M diatomic catalysts and using them to improve oxygen reduction performance is a promising approach for constructing high-performance zinc-air batteries and fuel cells.

[0144] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a Se-M diatomic catalyst, characterized in that: Includes the following steps: Synthesis of S1 and C2N: S1.1 Cyclohexanehexanone octahydrate and urea were ground and mixed to obtain a mixture; the mixture was heated to obtain an organic crosslinked compound; S1.2 The organic crosslinking material was ground and mixed with MgCl2 to obtain a mixed sample; the mixed sample was annealed under an inert atmosphere to obtain an annealed product; S1.3 The annealed product was placed in an acidic solution, stirred and etched, then washed and dried to obtain C2N; Synthesis of S2, Se-C2N: The C2N obtained in step S1.3 was ground and mixed with selenium dioxide and pyromellitic acid, and then annealed in an inert atmosphere to obtain Se-C2N; Synthesis of S3, Se-M diatomic catalysts: S3.1 Take Se-C2N and place it in anhydrous ethanol. Stir and then add acetylacetone metal salt. Mix well and then evaporate the ethanol to obtain a precursor mixture. S3.2 The precursor mixture was annealed under an inert atmosphere to obtain the Se-M diatomic catalyst SeM-C2N; In step S1.1, the molar ratio of cyclohexanehexanone octahydrate to urea is 1:4.5; the heating temperature is 70-100 ℃; and the heating time is 20-50 min. In step S1.2, the mass ratio of the organic crosslinker to MgCl2 is 1:2.5-6; the annealing temperature is 800-1100 ℃; and the annealing time is 1-3 h. In step S2, the mass ratio of C2N, selenium dioxide, and pyromellitic acid is 1:(0.5-1.5):(0-0.3). The annealing process is as follows: The annealing process includes two stages. The first stage annealing temperature is 200-400 ℃ and the first stage annealing time is 10-90 min. The second stage annealing temperature is 800-1100 ℃ and the second stage annealing time is 1-3 h. In step S3.1, the mass ratio of Se-C2N to acetylacetone metal salt is 10-30:1; the stirring time is 4-20 h; and the evaporation temperature is 60-100 ℃. In step S3.1, the acetylacetone metal salt is one of the following: iron acetylacetone, manganese acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, and molybdenum acetylacetone.

2. The method for preparing a Se-M diatomic catalyst according to claim 1, characterized in that: In step S1.3, the acidic solution is a 0.5 mol / L H2SO4 solution; the stirring time is 4-16 h.

3. The method for preparing a Se-M diatomic catalyst according to claim 1, characterized in that: In step S3.2, the annealing temperature is 800-1100 ℃; the annealing time is 1-3 h.

4. The Se-M diatomic catalyst is prepared by the preparation method according to any one of claims 1-3.

5. The application of the Se-M diatomic catalyst according to claim 4 in the electrocatalytic oxygen reduction reaction.

Citation Information

Patent Citations

  • C2N graphene composite precious metal nanometer catalyst and preparation method thereof

    CN106475081A